2023
DOI: 10.1186/s12951-023-01924-0
|View full text |Cite
|
Sign up to set email alerts
|

Zn-MOF hydrogel: regulation of ROS-mediated inflammatory microenvironment for treatment of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a chronic and recurrent inflammation disease associated with immune dysfunction. The high level of reactive oxygen species (ROS) causes high oxidative stress and further results in the deterioration of AD. At the same time, the ROS produced by bacterial infection can further aggravate AD. Here, the prepared PVA-based hydrogel (Gel) has a high ROS scavenging ability, and the antibacterial agent Zn-MOF(ZIF-8) loaded into the hydrogel shows a lasting and effective antibacterial activity.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Scale bars, 100 μm. q Relative quantification of mast cells [ 239 ]. Copyright 2023, Springer Nature …”
Section: Therapeutic Efficacy Of Nz@hydrogels In Clinically Relevant ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bars, 100 μm. q Relative quantification of mast cells [ 239 ]. Copyright 2023, Springer Nature …”
Section: Therapeutic Efficacy Of Nz@hydrogels In Clinically Relevant ...mentioning
confidence: 99%
“…Therefore, an effective approach for managing AD also involves the elimination of microbes and regulation of oxidative stress on the skin surface [ 233 ]. To address this issue, a recent study led by Qiu et al developed a hydrogel incorporating ZIF-8, referred to as Gel@ZIF-8 [ 239 ]. This hydrogel demonstrated remarkable ROS responsiveness, antibacterial effects, and high biocompatibility (Fig.…”
Section: Therapeutic Efficacy Of Nz@hydrogels In Clinically Relevant ...mentioning
confidence: 99%
“…Inorganic metal nanoparticles (NPs), such as silver (Ag), zinc(Zn), and copper (Cu), have been integrated into hydrogels to develop antibacterial biomaterials. [58][59][60][61] The bactericidal mechanism of metal ions is primarily attributed to their denaturing effect on bacterial proteins, rendering them effective for broad-spectrum bacterial control with minimal risk of drugresistant strains. Among these, silver (Ag) is widely employed as an antimicrobial agent, often incorporated as a physical coating within hydrogel systems.…”
Section: Antibacterial Hydrogelsmentioning
confidence: 99%
“…Notably, when ZIF-8 disintegrates, it continuously releases Zn 2+ , which is an excellent antibacterial agent. Numerous studies have demonstrated that using the original ZIF-8 or nanocomposites based on ZIF-8 may prevent bacterial invasion and facilitate pathogen removal, thereby preventing bacterial infection during the wound-healing process. However, ZIF-8 is typically obtained in the form of a fragile microcrystalline powder, which limits its applicability to use as a dressing for treating skin wounds.…”
Section: Introductionmentioning
confidence: 99%